2007
DOI: 10.1161/circulationaha.106.6806637
|View full text |Cite
|
Sign up to set email alerts
|

Protein Precoating of Elastomeric Tissue-Engineering Scaffolds Increased Cellularity, Enhanced Extracellular Matrix Protein Production, and Differentially Regulated the Phenotypes of Circulating Endothelial Progenitor Cells

Abstract: Background-Optimal cell sources and scaffold-cell interactions remain unanswered questions for tissue engineering of heart valves. We assessed the effect of different protein precoatings on a single scaffold type (elastomeric poly (glycerol sebacate)) with a single cell source (endothelial progenitor cells). Methods and Results-Elastomeric poly (glycerol sebacate) scaffolds were precoated with laminin, fibronectin, fibrin, collagen types I/III, or elastin. Characterized ovine peripheral blood endothelial proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 25 publications
(38 reference statements)
1
60
0
Order By: Relevance
“…the compressive resistance offered by hyaluronan, the critical roles performed by decorin and biglycan in tension and elastogenesis and yet the important contribution of decorin in collagen fibrillogenesis [25]. In this regard, Sales and colleagues [26] also found that cells expressing markers of SMC lineages segregate in the ventricularis of engineered porcine pulmonary valve leaflets [27]. Elastic fibers, which are insoluble in the valvular ECM, consist of macromolecules of cross-linked elastin surrounded by fibrillin-rich microfibrils, containing the RGD cell adhesion motif, which is capable of interacting with cell integrins, thus regulating cytoskeleton reorganization, cell proliferation and synthetic activities [28].…”
Section: Discussionmentioning
confidence: 99%
“…the compressive resistance offered by hyaluronan, the critical roles performed by decorin and biglycan in tension and elastogenesis and yet the important contribution of decorin in collagen fibrillogenesis [25]. In this regard, Sales and colleagues [26] also found that cells expressing markers of SMC lineages segregate in the ventricularis of engineered porcine pulmonary valve leaflets [27]. Elastic fibers, which are insoluble in the valvular ECM, consist of macromolecules of cross-linked elastin surrounded by fibrillin-rich microfibrils, containing the RGD cell adhesion motif, which is capable of interacting with cell integrins, thus regulating cytoskeleton reorganization, cell proliferation and synthetic activities [28].…”
Section: Discussionmentioning
confidence: 99%
“…Commonly used biomaterials are different copolymers and derivatives thereof, whereas, more recently, elastomeric materials have gained attention (Courtney et al 2006;Sales et al 2007;Stella et al 2010). Compared with decellularized xenogenic and allogenic matrices, these materials avoid the risk of disease transfer and immunological complications.…”
Section: Scaffolds For Heart-valve Tissue Engineeringmentioning
confidence: 99%
“…Fibronectin (Sigma-Aldrich Corp., St. Louis, MO) at 1.7 mg/ml in Hanks' buffered salt solution (Cambrex Corp.) was placed in the dishes at 48C overnight. Different protein precoatings clearly affect endothelial cell function (21). We chose fibronectin as the precoating agent for our experiments due to its ability to maintain cells attached to the silastic membrane for 6 hours at 15% strain.…”
Section: Cell Stretchmentioning
confidence: 99%